Lysosomes, curcumin, and anti-tumor effects: how are they linked? - Shen, Qian; Pan, Xue; Li, Yi; Li, Junchen; Zhang, Chuanlong; Jiang, Xiaochen; Liu, Fudong; Pang, Bo (Frontiers in Pharmacology, 2023)
Curcumin is a natural active ingredient from traditional Chinese medicine (TCM) that has multi-target characteristics to exert extensive pharmacological activities and thus has been applied in the treatment of various diseases such as cancer, cardiovascular diseases, nervous system, and autoimmune disorders. As an important class of membranous organelles in the intracellular membrane system, lysosomes are involved in biological processes such as programmed cell death, cell metabolism, and immune regulation, thus affecting tumor initiation and progression. It has been shown that curcumin can modulate lysosomal function through the aforementioned pathways, thereby affecting tumor proliferation, invasion, metastasis, drug resistance, and immune function. This review briefly elaborated the regulatory mechanisms of lysosome biogenesis and summarized curcumin-related studies with its anti-tumor effect, providing a reference for the clinical application of curcumin and anti-tumor research targeting lysosomes.